Pengaruh Kemahalan Harga, Return, Eps, dan Likuiditas Perdagangan Saham terhadap Keputusan Stock split - Winsa Septi Anggreini; Hari Setiono; Syaiful Bahri (CV. Kalimasada Group, 2025)
A stock split represents a strategic corporate action undertaken to realign share prices to more accessible levels, thereby enhancing their attractiveness to potential investors. This study examines the impact of stock price volatility, stock returns, earning s per share, and trading liquidity on the decision to execute a stock split. Employing a quantitative research design, the analysis utilizes logistic regression techniques. The empirical sample consists of eight financial sector firms listed on the Indonesia Stock Exchange that implemented stock splits between 2020 and 2024. The results indicate that both stock returns and earning s per share exert a statistically significant positive influence on stock split decisions. This implies that firms demonstrating higher returns and greater earnings per share are more inclined to pursue stock splits. In contrast, neither stock price volatility nor trading liquidity shows a significant association with such decisions. These findings suggest that stock split initiatives are predominantly driven by a firm’s financial performance rather than market perceptions of share prices or trading activity levels.